2022
DOI: 10.1002/adma.202201840
|View full text |Cite
|
Sign up to set email alerts
|

A Bionic Interface to Suppress the Coffee‐Ring Effect for Reliable and Flexible Perovskite Modules with a Near‐90% Yield Rate

Abstract: The certified champion power conversion efficiency (PCE) of perovskite solar cells (PSCs) has been impressively reported as high as 25.8%. [4] It is worth noting that the high-efficiency device is usually based on a thick, heavy, and fragile rigid substrate, which severely restricts roll-to-roll (R2R) manufacturing and diversified application scenarios. [5][6][7] Compared with the rigid ones, flexible PSCs have natural superiorities of lightweight and portable compatibility, [8][9][10][11] which boost a huge p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 57 publications
0
63
0
Order By: Relevance
“…received extensive attention and research to supplement some application scenarios where rigid devices cannot be applied. [3][4][5][6][7] The substrates of mainstream FPSCs are thermoplastic polymer materials polyethylene terephthalate (PET) and polyethylene naphthalate (PEN). [8,10] Due to the inherent characteristics of thermoplastic polymers, they will soften and bend during high temperature annealing process, resulting in poor thermal uniformity of the perovskite films.…”
mentioning
confidence: 99%
“…received extensive attention and research to supplement some application scenarios where rigid devices cannot be applied. [3][4][5][6][7] The substrates of mainstream FPSCs are thermoplastic polymer materials polyethylene terephthalate (PET) and polyethylene naphthalate (PEN). [8,10] Due to the inherent characteristics of thermoplastic polymers, they will soften and bend during high temperature annealing process, resulting in poor thermal uniformity of the perovskite films.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27] Flexible devices based on them not only have high power conversion efficiency (PCE) but also are lightweight. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] However, only around 1.1% elongation at break and fracture strength generally below 50 MPa limit the application of perovskite films in wearable devices. [43][44][45] Although some works attempted to increase the toughness of perovskite films, [46][47][48] the simultaneous improvement of strength and toughness is a huge challenge.…”
Section: Doi: 101002/aenm202202298mentioning
confidence: 99%
“…In addition to controlling solvent evaporation, regulating the microscale ink flow dynamics is also an effective way to control the nucleation and grain growth during the wet film drying process [112]. Huang and coauthors [59] reported a method for controlling the fluid drying dynamics by introducing a surfactant of L-α-phosphatidylcholine (LP).…”
Section: Blade Coatingmentioning
confidence: 99%